Contrast-enhanced mammography BI-RADS: a case-based approach to radiology reporting - Luca Nicosia; Ottavia Battaglia; Massimo Venturini; Federico Fontana; Manuela Minenna; Aurora Pesenti; Diana Budascu; Filippo Pesapane; Anna Carla Bozzini; Maria Pizzamiglio; Lorenza Meneghetti; Antuono Latronico; et al. (Insights into Imaging, 2024)
Abstract Contrast-enhanced mammography (CEM) is a relatively recent diagnostic technique increasingly being utilized in clinical practice. Until recently, there was a lack of standardized reporting for CEM findings. However, this has changed with the publication of a supplement in the Breast Imaging Reporting and Data System (BI-RADS). A comprehensive understanding of CEM is essential for further enhancing its role in both screening and managing patients with breast malignancies. CEM can also be beneficial for problem-solving, improving the management of uncertain breast findings. Practitioners in this field should become more cognizant of how and when to employ this technique and interpret the various CEM findings. This paper aims to outline the key findings in the updated version of the BI-RADS specifically dedicated to CEM. Additionally, it will present some clinical cases commonly encountered in clinical practice. Critical relevance statement Standardized reporting and a thorough understanding of CEM findings are pivotal for advancing the role of CEM in screening and managing breast cancer patients. This standardization contributes significantly to integrating CEM as an essential component of daily clinical practice. Key points • A complete knowledge and understanding of the findings outlined in the new BI-RADS CEM are necessary for accurate reporting. • BI-RADS CEM supplement is intuitive and practical to use. • Standardization of the CEM findings enables more accurate patient management. Graphical Abstract